Digital Technology: the Effect of Connected World to Computer Ethic and Family - Benfano Soewito; Sani Muhamad Isa (Bina Nusantara University, 2015)
The development of digital technology such as smartphones, tablets and other gadgets grows very rapidly in the last decade so does the development of mobile applications for those mobile systems or smartphones. Unfortunately, those applications often do not specify the age range for their users. This is actually a problem in the world of digital technology and software development. It is not yet known whether the applications is good be used for children or not. Nowadays, parents are faced with the dilemma of allowing their children to use these modern gadgets, which often lead to serious addiction or keeping them in the dark and risk raising ignorant kids. This research shows 80% of respondents agree or strongly agree that the gadget will affect to the development of children social skill. Therefore, in this research, the framework for ethical assessment is introduced and it can be applied to digital technology included gadget and its application in order to mitigate the negative effect of digital technology and gadgets.